Toward online multi‐period power dispatch with AC constraints and renewable energy. Issue 14 (4th July 2018) - Bie, Pei; Chiang, Hsiao‐Dong; Zhang, Buhan; Zhou, Ning
Abstract : In this study, a comprehensive online multi‐period power dispatch formulation that takes AC constraints, renewable energy, and ramping constraints into account is proposed. The AC power flow equations, voltage limits, and thermal limits are respected to ensure the obtained solution causes no static violation while guaranteeing transfer capability. A four‐stage solution methodology is proposed to solve the non‐linear constrained optimisation problem in which the thermal limit constraints are equivalently represented by active‐set‐based constraints in the third stage, and an adaptive homotopy‐enhanced primal‐dual interior point method (PDIPM) in solving power dispatch problem is presented in the fourth stage to reliably and efficiently obtain the solution. This solution methodology enhances both the robustness and speed of the PDIPM. The proposed four‐stage solution methodology has been evaluated on several testing systems, ranging from a 30‐bus system to a 3012‐bus system with four time periods, with promising results.